Factors affecting the usage of consumer mobile entertainment services in - Govender, Vinodhan (My University, 2011)
The South African mobile telecommunications market is very mature and close to saturation. The decline in subscriber growth rates coupled with regulatory pressures to reduce tariffs could have a serious negative impact on revenue growth and profitability for operators. The mobile operators, Vodacom and Cell C, have invested heavily in infrastructure deployment and data networks. Cell C is currently investing in the roll-out of its own data network. Consumer mobile entertainment services, which are delivered on the data networks, are a potential revenue stream which can provide the additional operators of revenues to compensate revenue lost due to decreases in voice tariffs that are being advocated by Parliament and the regulator, ICASA. The purpose of this research is to identify the factors that affect the usage of consumer mobile entertainment services in South Africa. Data was collected using a questionnaire survey that was administered in Gauteng. It was found that individuals between the age groups of 18 to 45 were currently the key users of consumer mobile entertainment services. However, the age group 46-55 showed the greatest propensity to adopt these services in the future. The mobile entertainment service categories that were the most frequently used were: Personalisation, Mobile and Infotainment services. However, Mobile TV, Infotainment, Mobile Video and Mobile Games showed the highest potential for future adoption. It was concluded from descriptive analysis and factor analysis that the five factors namely billing integrity, privacy and ethics associated with the service, iii good access (including bandwidth availability and transmission), availability (the ability to use the service from any location) and simplicity of use coupled with the appeal of the content, were indeed factors that would influence the adoption on consumer mobile entertainment services in South Africa. The ranking of these factors in order of importance were as follows: Accurately billed Private and ethical Easy to access Available anywhere; and Simple and entertaining Hence, when designing and developing consumer mobile entertainment services in South Africa, the offers should be promoted as being accurately billed, private and ethical, easy to access, available anywhere, and simple and entertaining. Network operators should concentrate on developing consumer mobile entertainment services for the following categories: mobile TV, infotainment, mobile video and mobile gaming service categories since they hold the greatest potential for future growth and adoption. Demographic analysis showed that the age group 46-55 exhibit the greatest growth potential. Operators should develop targeted campaigns at this segment encompassing the marketing, customer education and relevant content.
MBA - WBS
Keywords: Mobile telecommunications; Mobile entertainment; Cell phones